Reduced irradiation exposure areas enhanced anti-tumor effect by inducing DNA damage and preserving lymphocytes - Huiqin Chen; Yuan Li; Qiaofeng Shen; Guanqun Guo; Zhigang Wang; Hanyu Pan; Min Wu; Xueqing Yan; Gen Yang (Molecular Medicine)
Abstract Background Partial stereotactic body radiation therapy (SBRT) targeting hypoxic regions of large tumors (SBRT-PATHY) has been shown to enhance the efficacy of tumor radiotherapy by harnessing the radiation-induced immune response. This approach suggests that reducing the irradiation target volume not only achieves effective anti-tumor effects but also minimizes damage to surrounding normal tissues. In this study, we evaluated the antitumor efficacy of reduced-tumour-area radiotherapy (RTRT) , and explored the relationship between tumor control and immune preservation and the molecular mechanisms underlying of them. Methods In mouse breast cancer models, we compared the anti-tumor effects of RTRT and conventional radiotherapy (CNRT) by assessing tumor growth, metastasis, and survival rates. Additionally, we evaluated the peritumoral tissue damage and the immune microenvironment. The maturation of dendritic cells (DCs) and DNA damage induced by irradiated tumor cells were also assessed in vitro. Results In pre-clinical models, both RTRT and CNRT significantly inhibited primary tumor growth when compared to non-irradiated controls, with no significant difference between RTRT and CNRT. However, RTRT significantly extended survival times in mice, and increased the likelihood of inducing abscopal effects, thereby providing potential for better control of distant metastases. Further investigations revealed that the enhanced efficacy of RTRT may be attributed to the preservation of lymphocytes within the peritumoral tissue, as well as reduced damage to the surrounding skin and circulating lymphocytes. In vitro assays demonstrated that RTRT induced DNA damage and dsDNA in tumor cells, activating the cGAS-STING pathway. RTRT also triggered the release of damage-associated molecular patterns (DAMPs), which synergistically amplified the anti-tumor immune response. Conclusions Our findings suggested that appropriately narrowing the irradiation target volume effectively killed tumor cells while reducing damage to surrounding tissues, and preserving peritumoral lymphocytes. This approach improved the safety of radiotherapy while maintaining its efficacy in tumor control and provided an opportunity for combining high-dose radiotherapy with immunotherapy.